Cyclin G is involved in meiotic recombination repair in Drosophila melanogaster. - Nagel, A.C.; Fischer, P.; Szawinski, J.; La Rosa, M.K.; Preiss, A. (Journal of Cell Science, 2012)
Cyclin G (CycG) belongs to the atypical cyclins, which have diverse cellular functions. The two mammalian CycG genes, CycG1 and CycG2, regulate the cell cycle in response to cell stress. Detailed analyses of the role of the single Drosophila cycG gene have been hampered by the lack of a mutant. We generated a null mutant in the Drosophila cycG gene that is female sterile and produces ventralised eggs. This phenotype is typical of the downregulation of epidermal growth factor receptor (EGFR) signalling during oogenesis. Ventralised eggs are also observed in mutants (for example, mutants of the spindle class) that are defective in meiotic DNA double-strand break repair. Double-strand breaks (DSBs) induce a meiotic checkpoint by activating Mei-41 kinase (the Drosophila ATR homologue), thereby indirectly causing dorsoventral patterning defects. We provide evidence for the role of CycG in meiotic checkpoint control. The increased incidence of DSBs in cycG mutant germaria may reflect inefficient DSB repair. Therefore, the downregulation of Mei-W68 (an endonuclease that induces meiotic DSBs), Mei-41, or Drosophila melanogaster Chk2 (a downstream kinase that initiates the meiotic checkpoint) rescues the cycG mutant eggshell phenotype. In vivo, CycG associates with Rad9 and BRCA2. These two proteins are components of the 9-1-1 complex, which is involved in sensing DSBs and in activating meiotic checkpoint control. Therefore, we propose that CycG has a role in an early step of meiotic recombination repair, thereby affecting EGFR-mediated patterning processes during oogenesis.